Non-Invasive Brain Sensing Technologies for Modulation of Neurological Disorders - Salman Alfihed; Majed Majrashi; Muhammad Ansary; Naif Alshamrani; Shahad H. Albrahim; Abdulrahman Alsolami; Hala A. Alamari; Adnan Zaman; Dhaifallah Almutairi; Abdulaziz Kurdi; Mai M. Alzaydi; Thamer Tabbakh; et al. (Biosensors, 2024)
The non-invasive brain sensing modulation technology field is experiencing rapid development, with new techniques constantly emerging. This study delves into the field of non-invasive brain neuromodulation, a safer and potentially effective approach for treating a spectrum of neurological and psychiatric disorders. Unlike traditional deep brain stimulation (DBS) surgery, non-invasive techniques employ ultrasound, electrical currents, and electromagnetic field stimulation to stimulate the brain from outside the skull, thereby eliminating surgery risks and enhancing patient comfort. This study explores the mechanisms of various modalities, including transcranial direct current stimulation (tDCS) and transcranial magnetic stimulation (TMS), highlighting their potential to address chronic pain, anxiety, Parkinson’s disease, and depression. We also probe into the concept of closed-loop neuromodulation, which personalizes stimulation based on real-time brain activity. While we acknowledge the limitations of current technologies, our study concludes by proposing future research avenues to advance this rapidly evolving field with its immense potential to revolutionize neurological and psychiatric care and lay the foundation for the continuing advancement of innovative non-invasive brain sensing technologies.